Microstructural, thermal, electrical, and magnetic properties of optimized Fe3O4–SiC hybrid nano filler reinforced aluminium matrix composite - Ashrafi, Negin; Mohamed Ariff, Azmah Hanim; Sarraf, Masoud; Sulaiman, Shamsuddin; Tang, Sai Hong (Elsevier, 2021)
In the present study, the hybrid reinforcements (Fe3O4–SiC) novel composite has been successfully fabricated by powder metallurgy method. Adding Fe3O4 nanoparticles and SiC hybrid reinforcements in the aluminium matrix, improved the magnetic permeability of aluminium matrix composites as well as, thermal properties without mechanical degradation. In this study, the aim was to define the influence of SiC–Fe3O4 nanoparticles on microstructural, thermal, electrical, and magnetic properties of the composite. Based on obtained results, the highest density and hardness is 2.72 g/cm3 and 93 HV respectively. Adding (10–30 wt% SiC) into Al–15Fe3O4 slightly improved the magnetic saturation from approximately 2 to 6 (emu/g) and decreased coercivity from 238 to 177 G. The addition of (30 wt%) Fe3O4 nano particles and (10–20 wt%) SiC into aluminium resulted in magnetic saturation between 5 and 11.058 (emu/g) and decreased coercivity to 131G. Moreover, the thermal conductivity values at high weight percentage (30 wt %) of SiC was 190 W/mk. Increasing the SiC has improved the thermal conductivity of aluminium by 37%. Electrical resistivity of the Al–Fe3O4–SiC composites increased by adding Fe3O4 and SiC. By comparing all samples, Al-30 Fe3O4 -15 SiC can be selected as an optimization composite.